Communication Strategies Used by Middle Eastern Postgraduate Students at Service Encounters in University Malaya - Suo Yan Ju; Suo Yan Mei (European Journal of Language and Literature Studies, 2024)
European Journal of Language and Literature Studies May-August 2016 Volume 2 Issue 2